Analysis of Preventive Behaviors of Rural Tourism Hosts in the Face of COVID-19 Pandemic: Application of Health Belief Model - Mirakzadeh, Ali Asghar; Karamian, Faranak; Khosravi, Ehsan; Parvin, Fatemeh (Frontiers in Public Health, 2021)
The novel coronavirus (COVID-19) is one of the most severe public health crises in recent history. Therefore, in order to prevent the spread of COVID-19 and its negative effects on the health of rural tourist hosts and the rural community, it is necessary to pay attention to the conservation and health behaviors of rural tourist hosts. This study was conducted with the purpose of analyzing preventive behaviors of rural tourism hosts in the face of COVID-19 pandemic with the application of the health belief model (HBM) that is one of the most widely used models to study behavior to prevent and control diseases. In this study, all 80 tourism hosts of tourism target villages in Kermanshah province (the west of Iran), were studied as study population. A questionnaire was used to collect data which its validity and reliability were confirmed. Structural equation modeling (SEM) using Smart PLS software was used to analyze the data. The results of SEM indicated that perceived severity, perceived susceptibility, self- efficacy, perceived benefits, and cues to action accounted for 56% of the variance of “COVID-19 preventive health behavior” among the hosts of rural tourists in Kermanshah province. Moreover, the perceived susceptibility was the strongest predictor of preventive health behavior, while perceived barriers were not significant on behavior. Therefore, planning based on the HBM with emphasis on increasing awareness to improve and modify the health behavior of rural tourist hosts is recommended.